Birth Order and Psychology of Person: The Impact of Birth Order on Personality and Mental Health (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The child's ordinal position within the family's sibling hierarchy is linked to intellectual functioning, personality, behavior, and the development of psychopathology. The goal of this study was to look at the impact of birth order on personality and mental health. A study of (n=40) individuals found that one group (group I, n=20) was normal and the other (group II, n=20) was psychiatric. They were detained at the Pt. Deendayal Upadhyay Joint Hospital in Moradabad, Uttar Pradesh, India. GHQ-12 negative community members made up the normal group, which ranged in age from 20 to 30 years old. All of the participants in the research were given the Sentence Completion Test (SCT). The results showed that the ‘oldest' and ‘only' born psychiatric group had low ‘social', ‘ambitious,' and ‘confident' personality characteristics, and that the ‘oldest' male had higher mental morbidity than the female. At (p